Optimal work fluctuations for finite-time and weak processes - Nazé, Pierre [UNESP] (American Physical Society (APS), 2023)
The optimal protocols for the irreversible work achieve their maximum usefulness if their work fluctuations are the smallest ones. In this work, for classical and isothermal processes subjected to finite-time and weak drivings, I show that the optimal protocol for the irreversible work is the same for the variance of work. This conclusion is based on the fluctuation-dissipation relation W¯=ΔF+βσW2/2, extended now to finite-time and weak drivings. To illustrate it, I analyze a white-noise overdamped Brownian motion subjected to an anharmonic stiffening trap for fast processes. By contrast with the already known results in the literature for classical systems, the linear-response theory approach of the work probabilistic distribution is not a Gaussian reduction.